ANALISIS YURIDIS PERTIMBANGAN HUKUM HAKIM DALAM PERKARA NOMOR 60/Pdt.G/2024/PN Ptk - NIM. A1012211040, AINUN BERLIANTI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract This study examines Court Decisions in the context of Unlawful Acts. The formulation of the problem in this study is